Halal business management : a guide to achieving halal excellence - Tieman, Marco (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
'The halal industry is a fast-growing industry due to demographics and industry expansion. Halal certification of products, outlets, and services is essential for doing business in Muslim (majority) countries. This book shares the building blocks of professional halal business management, covering halal certification, halal supply chain management, halal branding & marketing, and halal risk & reputation management. Drawing on years of academic research and advisory experience, the book provides practical advice and guidance on how best to organise and upscale your halal business operations. Winning companies in the halal industry are those that embrace halal excellence by design. Halal excellence is a process, a pursuit of excellence. Halal business management is beyond halal certification, and needs to address also supply chain management, halal branding & marketing, and risk and reputation management. Halal excellence needs measurement through adopting the right key performance indicators, to protecting your halal reputation and licence to operate in Muslim markets. This book gives you proven, practical strategies to guide you in the halal industry. The book is for all of those organisations involved in serving Muslim markets as well as a course book for graduate and post graduate education in halal business management'--
Includes bibliographical references and index.
Keywords: Halal food industry -- Management; Halal food industry -- Marketing